Defunctioning stoma in rectal cancer surgery - A risk factor for Low Anterior Resection Syndrome?. Issue 12 (December 2022) - Pieniowski, E.H.A.; Nordenvall, C.; Johar, A.; Palmer, G.; Tumlin Ekelund, S.; Lagergren, P.; Abraham-Nordling, M.
Abstract: Background: In rectal cancer surgery the formation of a defunctioning stoma is common in order to reduce the consequences of an anastomotic leakage. The role of a defunctioning stoma and time to stoma reversal, in relation to major Low Anterior Resection Syndrome (LARS) in the long-term perspective, is still unclear. The aim of the study was to investigate the association between a defunctioning stoma and long-term bowel function. Method: Patients who underwent curative rectal cancer surgery between 2007 and 2013 in Stockholm county, Sweden, who had no history of anastomotic leakage, without a remaining stoma, free of cancer and alive in April 2017 were eligible for the study. The exposures were (i) use of defunctioning stoma at cancer surgery and (ii) time to stoma reversal. Main outcome was major LARS with information retrieved from the LARS score questionnaire. Multivariable logistic regression model was used to calculate odds ratios (OR) primary comparing major LARS to no LARS. Results: A total of 430 patients were included in analysis. The mean follow-up time was 6.7 years after surgery (range 3.4–10.7 years). The use of a defunctioning stoma was associated to major LARS with an adjusted OR of 2.43 (95% CI 1.14–5.20) when compared to no stoma. There were no evident associations between time to stoma reversal and the risk of major LARS. Conclusion: This study indicates that the presence of a defunctioning stoma is associated with impaired bowel function in the long-term perspective, while failing to show any clear association to time to stoma reversal.